ROZLICZANIE WYDATKÓW I NAKŁADÓW W POSTĘPOWANIU O ODZIAŁ MAJĄTKU WSPÓLNEGO MAŁŻONKÓW - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
Settlement of Inputs and Expenses in the Course of Proceedings Concerning Partition of Joint Property of Spouses Summary In the course of proceedings concerning partition of joint property of spouses, which are non-litigious proceedings (art. 566-567 of the Code of Civil Procedure), the court decide on the refunding of inputs and expenses from the joint property of spouses to separate property of spouses. According to the author in the course of proceedings concerning partitio of joint property of spouses the court shall consider inputs and expenses from separate property of spouses to their joint property not only „on application” but ex officio. This solution arises form the interpretation of the art. 45 of the Family Code and art. 567 of the Code of Civil Procedure.